HADIS SAFAR PEREMPUAN DALAM PERSPEKTIF MODERN: Analisis Hermeneutika Double Movement - Istifarin, Nur Annisa; Rochmawati, Ida (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
Hadiths that prohibit women from traveling without a mahram are often understood literally, without considering the socio-historical context in which the hadiths were revealed. This understanding has sparked controversy particularly in its application in modern society, which has undergone significant changes, such as improved travel safety and advancements in transportation technology. These changes necessitate a new approach that not only acknowledges the authority of the hadith texts but also aligns them with contemporary life dynamics. This qualitative research amploys a library research method. For the analysis process, it adopts Fazlur Rahman’s hermeneutic approach known as double movement, which empahasizes the importance of contextual understanding of hadith texts by considering the circumstances of the Prophet’s era nad their relevance in contemporary conditions. The findings reveal that the prohibition of women traveling without a mahram in the hadith was a response to the socio-historical conditions of that time, such as security concerns, travel risk, and the patriarchal culture that dominated Arab society. In modern contexts, these factors have significantly changed, especially with the advent of transportation technology, improved travel safety, and shifting social norms that support gender equality. Therefore, a literal approach is no longer relevant for rigid application. This study asserts that using Fazlur Rahman’s contextual approach allows these hadiths to be reinterpreted, resultingin a more relevant and inclusive understanding.